2016
DOI: 10.1109/tuffc.2016.2616172
|View full text |Cite
|
Sign up to set email alerts
|

Diverging Wave Volumetric Imaging Using Subaperture Beamforming

Abstract: Several clinical settings could benefit from 3-D high frame rate (HFR) imaging and, in particular, HFR 3-D tissue Doppler imaging (TDI). To date, the proposed methodologies are based mostly on experimental ultrasound platforms, making their translation to clinical systems nontrivial as these have additional hardware constraints. In particular, clinically used 2-D matrix array transducers rely on subaperture (SAP) beamforming to limit cabling between the ultrasound probe and the back-end console. Therefore, thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 23 publications
1
25
0
Order By: Relevance
“…An option could be the transmission of diverging waves having narrower aperture angles to scan each plane in several (e.g. 3) consecutive transmissions [67], [68]; this would reduce both the number of lines to be reconstructed for each transmission event and the energy spread over the region of interest with benefits in terms of CR and SNR without impacting on the achievable FR in real-time.…”
Section: Discussionmentioning
confidence: 99%
“…An option could be the transmission of diverging waves having narrower aperture angles to scan each plane in several (e.g. 3) consecutive transmissions [67], [68]; this would reduce both the number of lines to be reconstructed for each transmission event and the energy spread over the region of interest with benefits in terms of CR and SNR without impacting on the achievable FR in real-time.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that, as a general similarity measure metric, the proposed effective distance method can also be used in other imaging modality with the compounding process, such as the synthetic aperture imaging and diverging wave imaging [33, 34]. Further research on the application of the method will also be included in our next phase of work.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, beamforming is typically done in two phases where part of the beamforming is done in the transducer itself while the pre-beam formed signals are combined in the front-end in order to generate the individual image lines (i.e., two-stage beamforming [27]). Recently, it has been shown that severe imaging artifacts are introduced while using this technique for DWI [28]. This is due to delay errors which cause grating lobes and reduced penetration.…”
Section: Discussionmentioning
confidence: 99%